2018
DOI: 10.1093/nar/gky1271
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide mapping of Topoisomerase I activity sites reveal its role in chromosome segregation

Abstract: DNA Topoisomerase I (TopoI) in eubacteria is the principle DNA relaxase, belonging to Type 1A group. The enzyme from Mycobacterium smegmatis is essential for cell survival and distinct from other eubacteria in having several unusual characteristics. To understand genome-wide TopoI engagements in vivo, functional sites were mapped by employing a poisonous variant of the enzyme and a newly discovered inhibitor, both of which arrest the enzyme activity after the first transestrification reaction, thereby leading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 67 publications
1
24
0
Order By: Relevance
“…Encouraging evidence in support of the widely accepted twin-domain model, has established a greater understanding of topoisomerase activity during transcription and to a lesser extent replication. Topo II and topo I in eukaryotes exhibit higher levels of activity in the vicinity of highly transcribed genes [14,19], as has also been shown for mycobacterial topo I and gyrase [48]. Topo IV, on the other hand, demonstrates a clear preference for the dif site in E. coli [16,17], supporting the idea that decatenation is its primary cellular function [55].…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Encouraging evidence in support of the widely accepted twin-domain model, has established a greater understanding of topoisomerase activity during transcription and to a lesser extent replication. Topo II and topo I in eukaryotes exhibit higher levels of activity in the vicinity of highly transcribed genes [14,19], as has also been shown for mycobacterial topo I and gyrase [48]. Topo IV, on the other hand, demonstrates a clear preference for the dif site in E. coli [16,17], supporting the idea that decatenation is its primary cellular function [55].…”
Section: Discussionsupporting
confidence: 55%
“…This raises questions as to the determinants of topo binding and cleavage sites; how do the factors known to influence binding and activity including DNA topology and sequence play off against protein-mediated recruitment or inhibition in trans, and what other factors may influence topo binding and cleavage in vivo. It is clear the answer is not straightforward, with topo IB being directly recruited as part of the transcriptional machinery [19] and mycobacterial topo IA [48] and prokaryotic DNA gyrase [18] exhibiting more substantial DNA sequence preferences. As with all cellular processes, the mechanisms governing DNA topology maintenance are often not only protein specific but also species specific.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 28–32 ] Another set of newly developed methods, generally known as “genome wide” studies, allow identification of small variations in the genome itself or the association of specific proteins, such as polymerases and topoisomerases, to specific sites along the genome. [ 33–35 ] Although we recognize the value of the data obtained using all these different methods, here we restrict ourselves to discuss data obtained using 2D gels. For a detailed and excellent review of replication fork stalling at natural impediments see ref.…”
Section: Dna Replication Analyzed By Other Methodsmentioning
confidence: 99%
“…1B). Mutational analysis has shown that modification of the N- or C-terminal residues of this domain in Top1 from bacterial species, including Escherichia coli, Yersinia pestis, Mycobacterium tuberculosis and Mycobacterium smegmatis , will impair DNA religation, induce an SOS response and cause cell killing (10-14).…”
Section: Introductionmentioning
confidence: 99%